Effect of Bioenhancers on Amoxicillin bioavailability - Kalyani Barve; Kushal Ruparel (International Association of Physical Chemists (IAPC), 2015)
Amoxicillin, which inspite of being effective is losing its importance due to less bioavailability. Bioavailability could be enhanced by combining the antibiotics with bioenhancers like Piperine and Ginger resin. The present abstract deals with the use of piperine and ginger resin in increasing the bioavailability of amoxicillin using the insitu SPIP method. Piperine, isolated was found to be 99 % pure and ginger resin contained 4.36 % w/w of gingerol. The absorption of amoxicillin increased with addition of Piperine (1.2, 1.5, 1.8 % w/w of amoxicillin) in a dose dependant manner reaching saturation after 45 minutes wheras Ginger resin (6, 7, 8 % w/w of amoxicillin) failed to show this effect in the invitro studies. Piperine enhanced the permeation of Amoxicillin but ginger resin failed to show this effect using the insitu SPIP method. The method used may be appropriate for bioenhancers acting on transporters, metabolizing enzymes or modulators of diffusivity but not for those acting on gut motility. The combination of Piperine and Amoxicillin trihydarte may have a potential in reducing the dose, shortening the treatment period thus reducing drug-resistance problems of the antibiotic.